1996
DOI: 10.1007/bf02550854
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave lithotripsy monotherapy for bladder stones

Abstract: This report presents our initial experience in 36 patients with bladder stones, treated by extracorporeal shock wave lithotripsy. Minute fragmentation and uncomplicated evacuation occurred in 26 patients (72%). Mean treatment duration was 55 minutes. Mean number of shock waves was 3600 and electrical discharge averaged 24 kV per shock wave. No morbidity, during or after treatment, was encountered in these patients. The treatment was performed without the use of anaesthesia on an outpatient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 4 publications
0
11
0
2
Order By: Relevance
“…A cystoscopy was necessary to evacuate the calculi in 17% of patients. Kostakopoulos et al 14 reported 72% of patients free from calculi after ESWL in a series of 36 cases. Garcia Cardoso et al 15 performed ESWL in 45 patients and, after one to five sessions, 99.4% of patients were free of lithiasis, 13% of patients requiring cystoscopy assistance.…”
Section: Methods Methods Methods Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…A cystoscopy was necessary to evacuate the calculi in 17% of patients. Kostakopoulos et al 14 reported 72% of patients free from calculi after ESWL in a series of 36 cases. Garcia Cardoso et al 15 performed ESWL in 45 patients and, after one to five sessions, 99.4% of patients were free of lithiasis, 13% of patients requiring cystoscopy assistance.…”
Section: Methods Methods Methods Methodsmentioning
confidence: 98%
“…Fragmentation is obtained from sources of mechanical/ ballistic, ultrasonic, electro-hydraulic or laser energies. Several studies have demonstrated the superiority of the holmium: YAG laser compared to other lithotripsy methods [14][15][16][17][18][19] . Un-in et al 18 compared 23 patients undergoing lithotripsy with holmium: YAG laser with ten patients treated with ballistic lithotrispy.…”
Section: Methods Methods Methods Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Many previous studies presented promising data on its efficacy as a monotherapy in bladder stone. [9][10][11] Therefore, this retrospective study is conducted to explore the safety and effectiveness ofbladder stone management in the Cipto Mangunkusumo General Hospital (RSCM) who underwent ESWL. Patients who underwent ESWL were treated on supine position using PiezoLith 3,000 Plus -Richard Wolf.…”
Section: Medical Journal Of Indonesiamentioning
confidence: 99%
“…uric acid stones) have been well described. 19 Kostakopoulos et al, 11 Al-ansari et al, 20 and Telha et al 21 have also mentioned ESWL's role as a monotherapy in bladder stones fragmentation. The use of ESWL as a monotherapy in bladder stones, however, still has some controversial issues to address.…”
Section: 312-14mentioning
confidence: 99%